THE IMPROVEMENT OF STUDENTS’ ACADEMIC WRITING THROUGH READING ABILITY USING COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL - Rumiri Aruan (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2019)
This learning improvement study aims to improve teaching and learning outcomes in academic writing through reading ability by applying CIRC model. This research was conducted based on the problems that occur when students taking Academic Reading and Writing courses. Among the problems found is that students still find difficulties in writing a summary of the specified article. The research subjects were students in the fourth semester of the academic year 2018/2019. Before applying this method, the writer conducted a pre-test. The pre-test results showed that the students' writing summary skills were still low. The pre-test result was 2.77% of students scored very well, 19.43% got a good score, 27.77% of students scored moderately, 47.22% scored less, and 2.77% in the category of failure. The Classroom Action Research method is carried out in the application of the CIRC model which consists of two cycles, where each cycle took place in two meetings, and each cycle applied different learning activities. The results of the first cycle have shown changes in several assessment criteria, but the research was still being carried out into the second cycle. This was done to further strengthen learning by using the CIRC model. The percentage of student scores in the second cycle shows that 36.03% got a very good score, 33.33% got a good score, 30.55% got a sufficient score, and no more students scored less, and failed. From the above results can be concluded that the application of the CIRC model by the distribution of different discussion groups in each cycle affected learning outcomes. Thus the CIRC model can be considered to use in learning academic writing through reading ability in Academic Reading and Writing courses.